2002
DOI: 10.1046/j.1442-9993.2002.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

The late Quaternary vegetation history of the south‐central highlands of Victoria, Australia. II. Sites below 900 m

Abstract: The late Quaternary vegetation communities of the south‐central highlands of Victoria are constructed from analyses of pollen and charcoal, and macroscopic plant remains preserved in Sphagnum bogs. The sites, located in eucalypt forest or woodland, form an altitudinal sequence with the component Eucalyptus species varying with altitude and with small pockets of Nothofagus cunninghamii (Hook.) Oerst. in close proximity to the higher sites. The record from the sites above 900 m covers the last 32 000 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Nothofagus was more common near the treeline in the late Pleistocene in New Guinea, in cooler (although possibly cloudier and so less exposed to frost) conditions (Walker and Hope 1982;Hope 2009). The particularly high frost resistance recorded in N. cunninghamii may reflect substantial increases in frost resistance that evolved during glacial periods, particularly if refugia were colder and drier than is currently experienced (McKenzie 1995(McKenzie , 2002Worth et al 2009), and might involve more complex genetic change. However, frost resistance is the Figure 3.…”
Section: Responses To Freezing Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nothofagus was more common near the treeline in the late Pleistocene in New Guinea, in cooler (although possibly cloudier and so less exposed to frost) conditions (Walker and Hope 1982;Hope 2009). The particularly high frost resistance recorded in N. cunninghamii may reflect substantial increases in frost resistance that evolved during glacial periods, particularly if refugia were colder and drier than is currently experienced (McKenzie 1995(McKenzie , 2002Worth et al 2009), and might involve more complex genetic change. However, frost resistance is the Figure 3.…”
Section: Responses To Freezing Temperaturesmentioning
confidence: 99%
“…Even more remarkably, the regional palaeoenvironmental record does not contain a strong signature of prehistoric human activity. For example, Geoffrey Hope's extensive palynological and sedimentological studies of mountain mires in New South Wales and the ACT found no obvious signature of prehistoric burning that might be linked to human activity , a result that is replicated elsewhere in the region (Ladd 1979;Kershaw and Strickland 1989;Dodson et al 1994;McKenzie 1997McKenzie , 2002Mooney et al 1997). In contrast, many sites show a marked increase in charcoal associated with the appearance of Pinus pollen, marking the onset of European land management practices .…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that drier conditions earlier in the Holocene may have delayed this maximum. In south-central Victoria, forest reached current levels at several high-altitude sites after 11,500 cal BP (McKenzie 1997(McKenzie , 2002Kershaw et al 2007), but wet Eucalpytus forests and Nothofagus did not achieve maximum extent until ca. 7000 cal BP (McKenzie 2002).…”
Section: Climate Inferencesmentioning
confidence: 99%
“…In contrast, Tasmania and southeastern Australia, in part because of Peter Kershaw's long-standing interest, have many intensively investigated subalpine to alpine sites and a wealth of information on their treeline history (e.g. Kershaw and Strickland 1988;McKenzie 1997McKenzie , 2002Kershaw et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This has been achieved through the development and analysis of multiple pollen-based reconstructions, which have shown several common, and consistent, patterns. McKenzie (1997McKenzie ( , 2002 of several high-elevation (>900 m) sediment cores that have been dated to ca. 31,500 BP and again from 20,000 BP, at which point the N. cunninghamii pollen are found continuously until the present, albeit with fluctuating abundance.…”
Section: Evidence From Pollenmentioning
confidence: 99%